Rancang Bangun Aplikasi Game First Person Shooter Pendaratan Jepang di Minahasa - Ludong, Andrew Paulus; Narasiang, Benefit S.; Paturusi, Sary D.E. (Jurnal Teknik Informatika, 2021)
Abstract — History is indeed discussing something that already passed or ancient, however, of course, there are reasons why important events are made into history, namely to be remembered and studied. It is important for us to study important events, especially those that happened in the areas where we live. However, apart from only having a few sources to learn history, the media used is not so entertaining especially among young people. Therefore, we must change the media we used to learn history, so that it is more appealing to the community, especially among young people as the nation's next generation. The game market in Indonesia is one of the largest in Southeast Asia and continues to grow. Therefore, we can use games as a media for learning history. In fact, one of the most popular game genres in Indonesia today is shooter games. This study aims to produce a game that introduces the history of Japanese landings in Minahasa, a game with first-person shooter genre. The method used is MDLC (Multimedia Development Life Cycle). This game will be built using Blender and Unity3d.    Keywords — Game; History; Minahasa; War     Abstrak — Sejarah memang membahas sesuatu yang lampau atau sudah kuno, meskipun begitu, peristiwa penting dijadikan sebuah sejarah tentu ada alasannya, yaitu untuk diingat, dikenang dan dipelajari. Penting bagi kita untuk mempelajari peristiwa penting, terlebih yang terjadi di daerah yang kita tinggali. Namun demikian, selain sumber pembelajaran sejarah sedikit, medianya pun kurang begitu menghibur terlebih dikalangan anak muda. Maka dari itu, kita harus merubah media pembelajaran sejarah agar lebih diminati masyarakat terlebih kalangan anak muda sebagai generasi penerus bangsa. Pasar game di Indonesia adalah salah satu yang terbesar di Asia Tenggara dan terus berkembang, dengan begitu kita bisa menggunakan game sebagai media pembelajaran sejarah. Bahkan salah satu genre game yang paling diminati di Indonesia saat ini adalah game shooter. Penelitian ini bertujuan untuk menghasilkan game yang memperkenalkan sejarah pendaratan Jepang di Minahasa, sebuah game bergenre first person shooter. Metode yang digunakan adalah MDLC (Multimedia Development Life Cycle). Game ini akan dibangun menggunakan Blender dan Unity3d.     Kata kunci — Game; Minahasa; Perang; Sejarah